1980
DOI: 10.1021/ja00539a003
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic barriers in nucleophilic displacements

Abstract: equation,26 and HSAB theory20 have all been used in attempts to correlate reactivity with structural or thermodynamic properties. Success of these correlations is rather limited, as absolute and even relative rates of SN2 reactions have been found to be highly solvent (2) (a) Swain, C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
81
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(93 citation statements)
references
References 5 publications
11
81
0
Order By: Relevance
“…The energy then increases as the reaction proceeds to the transition state and this transition state has a lower electronic energy than the reactants [16]. These theoretical results are in agreement with the experimental ones [5,6] which may be represented by potential-energy profiles with a double minimum [3,40].…”
Section: S N 2 Reactions Through Ab Initio Calculationssupporting
confidence: 87%
“…The energy then increases as the reaction proceeds to the transition state and this transition state has a lower electronic energy than the reactants [16]. These theoretical results are in agreement with the experimental ones [5,6] which may be represented by potential-energy profiles with a double minimum [3,40].…”
Section: S N 2 Reactions Through Ab Initio Calculationssupporting
confidence: 87%
“…[7,18] This uncertainty, due to the lack of solvation in the theoretical approach, was demonstrated when research indicated that the solvation energy for simple organic reactions was large and that the free energies of activation including solvent were very different from those calculated in the gas phase. This solvation problem was also demonstrated by the work of Bohme and co-workers [19] and others [20,21] who showed that the reaction coordinate was different for S N 2 reactions in the gas phase and in solution. Another problem that plagued the theoretical approach to determining transition-state structure was that only the largest computers were able to calculate the structure of even medium-sized molecules accurately.…”
Section: Introductionmentioning
confidence: 74%
“…This was done so that the enthalpy of activation could also be used to assess the results from the different theoretical methods in which solvation was included in the calculations. The activation parameters were not calculated for the gas-phase models in which the reaction coordinate [20,21] and the activation parameters are very different from those in solution. [19] The theoretical models: Forty-two different theoretical methods have been used to calculate the structure of the transition state and the experimental KIEs for the ethyl chloride ± cyanide ion S N 2 reaction for an S N 2 reaction.…”
mentioning
confidence: 99%
“…In Equation (12), k o refers to the rate of a standard reaction, and k is the rate of the reaction of the nucleophile under consideration. The parameter s is the sensitivity of the given substrate.…”
mentioning
confidence: 99%